Teach yourself visually PCs - Marmel, Elaine J. (Teach yourself visually, 2011)
Clear, step-by-step screen shots show you how to tackle more than 150 common PC tasks. Each task-based spread covers a single technique, sure to help you get up and running on your computer in no time